Multi-institutional phase 2 study of TLK286 (TELCYTA™, a glutathione S-transferase P1-1 activated glutathione analog prodrug) in patients with platinum and paclitaxel refractory or resistant ovarian cancer. Issue 4 (1st June 2005) - Kavanagh, J. J.; Gershenson, D. M.; Choi, H.; Lewis, L.; Patel, K.; Brown, G. L.; Garcia, A.; Spriggs, D. R.
Abstract : The purpose of this study was to determine the safety and efficacy of TLK286 (TELCYTA™), a glutathione analog prodrug, in patients with platinum and paclitaxel refractory or resistant ovarian carcinoma. Thirty-six patients with measurable disease were enrolled. TLK286 was administered at 1000 mg/m 2 intravenously every 3 weeks. The endpoints were objective response rate assessed by Response Evaluation Criteria in Solid Tumors (RECIST) and survival. Adverse events were graded using the National Cancer Institute Common Toxicity Criteria. Thirty-four platinum refractory or resistant patients (94%) were evaluable for objective tumor response. Five patients (15%) had objective tumor responses, including one durable complete response (CR) of greater than 3 years and continuing. The disease stabilization rate was 50%, including one CR (3%), four partial responses (12%), and 12 durable disease stabilizations (35%). Responses were accompanied by improvement in clinical symptoms and Eastern Cooperative Oncology Group Performance Status (ECOG PS) and decline in CA125 levels. Median survival was 423 days with survival of 60% at 1 year and 40% at 18 months. TLK286 was well tolerated in this population. TLK286 is an active agent in chemotherapy-resistant ovarian cancer. Further studies of TLK286 in platinum and paclitaxel refractory or resistant ovarian cancer are in progress.